Delito y sociedad: un análisis crítico de la justicia penal - Anrrango Mesa, Edwin Raul; Campaña Bustamante, Janela Alejandra; Encalada Echeverría, Ana Lucía; Gómez Sierra, Betty Verónica; Herrera Pozo, Pablo Aníbal; Inuca Morales, Lilian Maribel; Landázuri López, Paola Cristina; Lopez Salinas, Carmen Magdalena (Editorial Grupo AEA, 2026)
The book Crime and Society: A Critical Analysis of Ecuadorian Criminal Justice offers an in-depth reflection on the structure, evolution, and challenges of the criminal justice system in Ecuador. Through an interdisciplinary approach that combines law, criminology, sociology, and forensic medicine, the work examines how the state responds to crime, the tensions between security and human rights, and the reforms necessary for a more equitable justice system. Over five chapters, it analyzes the history and principles of Ecuadorian criminal law, the theory of crime and punishment, the legal construction of criminal responsibility, alternatives to imprisonment, and conditions in the prison system. It also addresses the relationship between criminal justice, criminal policy, and society, highlighting the influence of punitive populism and the criminalization of poverty. The text proposes a critical vision aimed at the structural transformation of the judicial system, promoting restorative justice, rehabilitation, and social reintegration. With a solid and upto- date analysis, the work establishes itself as an indispensable academic contribution to understanding the contemporary challenges of Ecuadorian criminal justice and its relationship with human rights.